(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the risk of preterm birth in younger pregnant females. Study Design: Retrospective study, Place and Duration of Study: This study was carried out at the Obst. and Gynae National Hospital Sargodha from September 2011 to December 2011. Materials and Methods: All of the 76 women who were admitted with preterm labor were included in the study. They were assessed according to ACOG criteria. The admitted patients were managed according to the standard protocol. Gestational age was calculated and preterm pregnancy was confirmed by scan. Associated maternal risk factors and pregnancy complications were also evaluated. Results: There were 76 women who admitted with the complaint of preterm labor. Out of these, 29 (38%) were in true labor and delivered. Rest of them was in threatened labor and managed accordingly. 69.7 % of the women who delivered as preterm were in the age group of 15 -25 years. Associated maternal risk factors and pregnancy complication were also determined. Conclusion: It is concluded from this study that preterm labor associated with preterm birth is more prevalent in younger pregnant females.